The impact of customer trust, customer identification and customer satisfaction towards customer loyalty in banking sector / Shahrul Ridzuan Jamari - Jamari, Shahrul Ridzuan (Faculty of Business and Management, 2018)
The purpose of this study is to identify the impact of customer trust, customer identification and customer satisfaction towards customer loyalty in banking sector. The research is based on a sample of 136 respondents. The results show that Customer trust, Customer identification and Customer satisfaction have significant influence on customer loyalty in banking sector. The emergence of new banking channels like as phone banking, Internet banking, Automated Teller Machines (ATM), furthermore developing financial market & global competition have constrained bankers to explore the importance of customer loyalty. For the banks to be successful in the intensively competitive environment, they are bound to attach importance to customer loyalty. Results of the current study reveal that customer trust, customer identification and customer satisfaction have significant effect on customer loyalty. Moreover, the study revealed that customer trust is found as the most influential variable for customer loyalty. The managerial implication of this research is the considerations of bank managers for the enhancement of their customer loyalty.